Pengaruh Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian : (Survei Konsumen Pada Perusahaan Sandal Nandar Jaya Tasikmalaya) - Asep Suhendar Aprilia (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This study aims to determine the simultaneous and partial effect of product quality, promotion, Purchasing Decisions At The Sandal Nandar Jaya Company, Tasikmalaya City. The method used in this research is a survey research method. Research data obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS. The results of this study indicate that product quality, promotion, simultaneously significant effect on purchasing decisions. Promotion has a significant effect on purchasing decisions. product innovation has a significant effect on purchasing decisions.